Comparison of c-MYC Expression between Patients with Germinal Center and Non-Germinal Center B-cell-like Diffuse Large B Cell Lymphoma - Hanum, Sitti Fatimah; Hardjolukito, Endang Sri Roostini; Kusmardi, Kusmardi; Murtiani, Farida; Widiantari, Aninda Dinar; Setiawaty, Vivi (http://dharmais.co.id/, 2025)
Background: c-MYC expression has been used as a prognostic marker to predict prognosis and determine therapeutic strategies in both Diffuse Large B Cell Lymphoma (DLBCL) subtypes. No study on c-MYC expression associated with DLBCL has ever been conducted in Indonesia. Our study aimed to evaluate differences in c-MYC expression in both DLBCL subtypes and assess the immunophenotype profile.Method: We selected 40 DLBCL cases and divided them into Germinal Center B-cell (GCB) and non-GCB subtypes using Hans Criteria. We evaluated c-MYC expression, and a cut-off value of 60.4% was determined using Receiver Operating Characteristic (ROC) curve analysis.Results: We found that c-MYC expression was significantly higher in GCB subtypes compared to non-GCB subtypes (n = 17 (42.5%) vs n = 20 (7.5%), p 0.000 and mostly had an immunophenotype of CD10+/BCL6+/MUM1+.Conclusion: Higher c-MYC expression is found more frequently in GCB subtypes. These findings suggest that c-MYC may play a subtype-specific role in DLBCL pathogenesis, potentially influencing therapeutic decisions for Indonesian patients. Future studies should validate these results in larger, multi-center cohorts and explore the mechanistic link between c-MYC and the GCB subtype and its clinical implications for targeted therapies.